Disparities, Discrepancies and Specific Concentration – Diversification Trends in the Group of Central and East European Ex-Socialist Countries - Gheorghe Săvoiu; Marian Siminică (Amfiteatru Economic Journal, 2016)
The paper identifies some major disparities and quantifies some discrepancies and gaps, as well as specific trends of concentration-diversification in today's group of the 11 former socialist economies of Central and Eastern Europe (CEEC). After a brief introduction describing the approach based on multiplied research focused on the ex-socialist economies in CEEC that have already acceded to the European Union (EU), a special section is devoted to the statistical concepts that are measurable and applied in this paper, i.e. disparity and gap or discrepancy, finally detailing an original research method that capitalizes on these statistical tools with matrices and econometric models (including those focused on associations, correlations and concentration-diversification coefficients). A set of major variables are analyse and discussed in parallel with some trends that have already been presented in the international literature, outlining the specifics of CEEC economies in the context of their real convergence to the EU average level (EU-28 and EU-16). A few final remarks identify some paradoxes of the economies analysed.
Keywords: C10; C19; C59; O47; O52; 330; disparities; gaps; concentration-diversification; convergence; Gini-Struck coefficient; ex-socialist Countries in Central and Eastern Europe (CEEC)